The influence of life experience, self-evaluation, beauty privilage on the self-confidence attitude of college students in Yogyakarta - Binta Askhani, Naela; Khilmiyah, Akif (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Self-confidence is a crucial psychological attribute that shapes students’ academic performance, social interactions, and personal development. Factors such as life experience, self-evaluation, and beauty privilege play a significant role in influencing how college students in Yogyakarta perceive and express their confidence. This study aims to determine the effect of life experience, self-evaluation, and beauty privilege on the self-confidence of female college students in Yogyakarta. This study uses a quantitative approach with a survey method. The sample consisted of 300 female students from several universities in Yogyakarta who were selected by purposive sampling technique. The instrument used is a scale that has been validated and tested for reliability. The results of multiple regression analysis showed that the three independent variables of life experience, self-evaluation, and beauty privilege simultaneously had a significant effect on the self-confidence of female students. Partially, self-evaluation contributes the most, followed by life experience, while beauty privilege has a smaller but still significant influence. The findings suggest that self-confidence is not only determined by internal factors such as self-evaluation, but also by life experiences and perceptions of physical attractiveness. This research contributes to the development of strategies to increase the confidence of female college students through psychological and social approaches.